2005
DOI: 10.1007/s10499-004-9022-6
|View full text |Cite
|
Sign up to set email alerts
|

Perspectives for development of low impact aquaculture in a Western Mediterranean lagoon: the case of the carpet clam Tapes decussatus

Abstract: Abstract. Some 30,000 specimens of the Mediterranean clam Tapes decussatus were suspended in nylon bags of two different mesh sizes and pre-grown in the Calich lagoon (Sardinia, Italy) from March to June 2001. The samples differed in size at the end of the pre-growth stage. They were then sown at a density of 650 specimens m )2 in two stations of the lagoon. The growth rates in the stations were different according to the Von Bertalanffy model. Primary and secondary plankton production was calculated by field … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 6 publications
0
12
0
Order By: Relevance
“…In Turkey, this species is distr ibuted along the coastline of Aegean, Mediterranean and Marmara Seas. Th is species is a leading candidate for aquaculture in Turkish waters, similar ly to other Mediterranean lagoons (Chessa et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…In Turkey, this species is distr ibuted along the coastline of Aegean, Mediterranean and Marmara Seas. Th is species is a leading candidate for aquaculture in Turkish waters, similar ly to other Mediterranean lagoons (Chessa et al, 2005).…”
Section: Introductionmentioning
confidence: 90%
“…For example, Serdar et al (2007) reported 48% survival rate for R. decussatus after 12 months in Homa estuary, İzmir, in western Turkey. Chessa, Paesanti, Pais, Scardi, Serra & Vitale (2005) reported a survival rate of 50% for R. decussatus in Calich Estuary, Italy, at the end of 15 months. Typically, a 50% survival rate was reported for manila clam juveniles until they reach commercial size in Italy (Sladonja, Bettoso, Zentilin, Tamberlich & Acquavita, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…In Europe, the harvesting of Venerupis decussata mainly occurs in countries like Spain and France, but also in Italy, especially in Sardinia, where the semi-extensive culture of the allochthonous species Venerupis philippinarum has been banned by the Regional Government in order to protect the native Mediterranean carpet clam (Chessa et al, 2005;Pais et al, 2006b).…”
Section: Grooved Carpet Shell Distribution Habitat and Exploitationmentioning
confidence: 99%
“…Furthermore, a number of successful trials have demonstrated the feasibility of rearing this bivalve in different European countries (Walne, 1976;Breber, 1985;Pastore et al, 1996) using different culture techniques in the sea as well as in coastal lagoons (Chessa et al, 1998(Chessa et al, , 2005Pais et al, 2006b;Serdar et al, 2007).…”
Section: Rearing In Europementioning
confidence: 99%